Complete mitochondrial genome of Drabescoides nuchalis (Hemiptera: Cicadellidae). (2nd September 2016) - Wu, Yunfei; Dai, Renhuai; Zhan, Hongping; Qu, Ling
Abstract: The complete mitochondrial genome (mitogenome) of Drabescoides nuchalis (Hemiptera: Cicadellidae) was sequenced. It is 15 309 bp in length with 75.62% (A + T) content and comprises 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNA genes, and a non-coding region (GenBank accession no. KR349344). Gene order is identical to that of the inferred ancestral insect genome. All PCGs start with an ATN codon and terminate with TAA except ND4, which has an incomplete stop codon (T). The anticodons are identical to those of Drosophila yakuba . The phylogenetic tree confirms D. nuchalis and two Cicadellidae species are clustered into a clade, and Cicadellidae is a monophyletic group and provides support for the sister relationship of leafhopper and treehopper.